The process of translating puns and jokes between languages - Jasurbek Khonimkulov, Abduvokhidov Javohir Abduvohidovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article analyzes the process of translating puns and jokes from one language into another from linguistic and cultural perspectives. As puns and humor are deeply rooted in the phonetic, lexical-semantic, and cultural features of a language, their translation poses significant challenges. The study systematically examines the main problems encountered during translation and discusses strategies such as literal translation, cultural adaptation, functional substitution, and explanatory translation. The author emphasizes the importance of preserving the emotional and communicative functions of humor in the new cultural context. This research holds theoretical, methodological, and practical significance for translation studies and may be useful for scholars and professional translators.